Marketing ambiental - PIRES, Amanda Thayna; DORTA, Gabrieli; OLIVER, Maria Laura de Souza; RODRIGUES, Victor Eduardo (255, 2016)
O tema Marketing Ambiental será apresentado para abordar os direitos e deveres das empresas que efetuam as atividades do marketing verde, mostrando também seus benefícios que esta ação causa para as empresas, consumidores, governo público e para o ecossistema. A fim de estimular essa prática e conscientizar as empresas de sua responsabilidade com o meio-ambiente, o artigo também aborda assuntos como: selos sustentáveis e logística reversa. Essa ação é vista como uma inovação de mercado, o que permite atrair mais consumidores, pois com o passar do tempo vem percebendo a importância da responsabilidade ambiental, assim cobrando também das empresas.

The environmental marketing theme will be presented to bring up subject about rights and the duties of the companies that do activities of the green marketing showing the benefits this action causes to the companies, consumers, public government and also to the ecosystem. In order to stimulate this practice and aware the companies about your responsibilities with the involvement, the article also bring up points such as: sustainable stamps and reserve logistic. This action is seen as logistic marketing innovation, which makes it draws more consumer, because as time goes start realizing the matter of the environmental responsibilities, charging the companies, as will.
Environmental marketing
Keywords: Empresas; Marketing; Gestão e Negócios